An investigation into proverbs With words denoting humans In english and vietnamese - Bùi Thị Hoàng Mai (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In linguistics, the proverbs are the object of numerous studies not only because they are generally known as the quintessence of a people’s collective wisdom but also because they are form-meaning units which exhibit the traditional status, the prosodic form, the didactic value, the rustic imagery. Thus, the purpose of this study is to conduct a contrastive analysis on proverbs containing words denoting humans in English and Vietnamese (EPsWH and VPsWH). This research focuses on the semantic and syntactic features of the proverbs containing words denoting human in the two languages to find out the similarities and differences between them. However, some stylistic devices are also presented at the same time to clarify sense relations of proverbs. A number of samples from dictionaries, magazines, books are selected and categorized in terms of syntactic, semantic and stylistic devices to serve the purpose of investigation stated. The findings of this research reveal that the syntactic features of proverbs containing words denoting human in the two languages such as phrases, sentences, and structures are identical to some extent. However, in the semantic aspect, the occurrence of semantic fields is not the same in English and Vietnamese. One more noticeable difference has also been discovered in the study process is that a PWH in Vietnamese can have an equivalent without words denoting human in English or vice versa. This increases the problems of loss and gain in proverb translation. Also, many stylistic devices such as simile, metaphor, antithesis, hyperbole are frequently applied as the expressive means in PsWH in the two languages. In contrast, no metonymy can be found in the corpus of VPsWH. Along with these findings, the research is expected to offer teachers, learners, or translators some aids in understanding, using and translating PsWH with the hope that they will be able to partly deal with the obstacles of languages and cultures in communication.